A halogen bond route to shorten the ultrashort sextuple bonds in Cr2 and Mo2. Issue 58 (5th July 2017) - Joy, Jyothish; Jemmis, Eluvathingal D.
Abstract : Selective extraction of destabilizing σ-electrons from the sextuple bond of Cr2 and Mo2 via σ-hole on a halogen bond donor shortens and strengthens the ultra-short metal–metal bond. Abstract : Sextuple bonded group 6 diatomics Cr2 and Mo2 possess ultrashort metal–metal bonds. Yet their bond dissociation energy is very low. The destabilising nature of σ-bonds is responsible for this. Selective extraction of these σ-electrons via a σ-hole on a halogen bond donor shortens and strengthens the metal–metal bond. This study constitutes a hitherto unexplored application of halogen bonding and an example for the true violation of bond order–bond strength relation.